ANALISIS SWOT TERHADAP USAHA TOKO IMELDA PONSEL TELUKDALAM NIAS SELATAN - Paskalis Dakhi; Progresif Buulolo (Balance: Jurnal Riset Manajemen dan Bisnis, 2022)
Imelda Ponsel Telukdalam South Of Nias is store in Nias is a trade in electronic goods and specifically mobile phones in various brand. The study is intended to answer how and whether the Imelda ponsel store platform a swot strategy on its business. The method of data analysis technique with a descriptive qualitative approach. Based on the analysis of the swot strategy to its business, which can be proven from the analysis of the internal and external or factors IFAS and EFAS, and thus the coordinate poin of 1.724 : 1.01 on the swot diagram eksplains that the mobile imposition store is in the province supporting the growth/growth strategy an the enterprise is still in prime condition. These condition provide an opportunity for maximum profits because companies have the opportunity and the power to do both development and expansion of busineses.